An improved method with high sensitivity and low background in detecting low β-galactosidase expression in mouse embryos - Shen, Xiaopeng; Bao, Wenjing; Yu, Wei; Liang, Rui; Nguyen, Bao; Liu, Yu (PLOS ONE, 2017)
LacZ is widely used as a reporter in studies of gene expression patterns. β-galactosidase, the product of LacZ gene, is usually detected by X-gal/FeCN staining. In X-gal/FeCN staining, β-galactosidase catalyzes X-gal to produce blue precipitates, which indicate the expression patterns of the gene of interest. A newer LacZ detection method using S-gal/TNBT is more sensitive but plagued by high background. Here, we describe an improved procedure that combines advantageous steps from the two methods. By comparing with X-gal/FeCN and S-gal/TNBT methods in detecting the expression patterns of miR-322/503 and miR-451 at a series of developmental stages, the improved method showed higher sensitivity and lower background. Thus, the improved method could be an alternative way of β-galactosidase staining in low gene expression situations.